Effect of lipid-bound apolipoprotein A-I cysteine mutant on ATF3 in RAW264.7 cells. Issue 1 (3rd February 2017) - Wang, Yunlong; Wang, Yanhui; Jia, Shaoyou; Dong, Qingzhe; Chen, Yuanbin; Lu, Shulai; Hou, Lin
Abstract : Activating transcription factor 3 (ATF3) is a TLR-induced repressor that plays an important role in the inhibition of specific inflammatory signals. We previously constructed recombinant high density lipoproteins (rHDL) (including rHDLWT, rHDLM, rHDL228 and rHDL74 ) and found that rHDL74 had a strong anti-inflammatory ability. In the present study, we investigate the roles of recombinant apolipoprotein A-I (ApoA-I) (rHDLWT ) and its cysteine mutant HDLs (rHDLM, rHDL228 and rHDL74 ) on ATF3 function in RAW264.7 cells stimulated by lipopolysaccharide. Our results showed that compared with the LPS group, rHDL74 can decrease the level of TNF-α and IL-6, whereas rHDL228 increases their expression levels. RT-PCR and Western blotting results showed that compared with the LPS group, rHDL74, rHDLWT and rHDLM can markedly increase the expression level of ATF3, whereas the level of ATF3 decreases in the rHDL228 group. In summary, the different anti-inflammatory mechanisms of the ApoA-I cysteine mutants might be associated with the regulation of ATF3 level.